REVEALING MURDERER AS REFLECTED IN ARTHUR CONAN DOYLE’S THE HOUND OF THE BASKERVILLES - Husna, Atikasari; Multazim, Akhmad; Wahyuningrum, Upik (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
The era of technology and globalization triggers various new crimes like murder with various motives. The objectives of this research are to reveal the intrinsic elements of the novel and to describe the efforts of the main character to reveal the murder of the story. There are two kinds of data in this research: primary data and secondary data. The primary data are taken from the novel The Hound of the Baskervilles by Arthur Conan Doyle. The secondary data function to support the primary data and add more information that is related to this novel. Data were gathered, classified, analyzed and interpreted by using several theories. The results of the research shows that the intrinsic elements are described based on theme, setting, character and characterization, plot and point of view. The efforts of the main character to reveal the murder are: (a) analyzing the report and interviewing the witnesses, (b) solving the problem on the investigation, (c) investigating the murder case secretly and (d) building the strategies to reveal the criminal